Five OsS40 Family Members Are Identified as Senescence-Related Genes in Rice by Reverse Genetics Approach - Habiba; Xu, Jiaxuan; Gad, Ahmed G.; Luo, Yuling; Fan, Chunlan; Uddin, Junaite Bin Gias; ul Ain, Noor; Huang, Chengxin; Zhang, Yu; Miao, Ying; Zheng, Xiangzi (Frontiers in Plant Science, 2021)
A total of 16 OsS40 genes of Oryza sativa were identified in our previous work, but their functions remain unclear.. In this study, thirteen OsS40 members were knocked out using the CRISPR/cas9 gene-editing technology. After screening phenotype characterization of CRISPR/Cas9 mutants compared to WT, five oss40s mutants exhibited a STAY-GREEN phenotype at 30 days after heading. Moreover increased grain size and grain weight were occurred in the oss40-1, oss40-12 and oss40-14 lines, while declined grain weight appeared in the oss40-7 and oss40-13 mutants. The transcript levels of several senescence-associated genes (SAGs), chlorophyll degradation related genes (CDGs), as well as WRKY members were differentially decreased in the five STAY-GREEN oss40s mutants compared to WT. Five oss40 mutants also exhibited stay-green phenotype when the detached leaves were incubated under darkness for 4 days. OsSWEET4 and OsSWEET1b were significantly upregulated, while OsSWEET1a and OsSWEET13 were significantly downregulated in both oss40-7 and oss40-14 compared to WT. Furthermore, these five OsS40 displayed strong transcriptional activation activity and were located in the nucleus. Most of the OsS40 genes were down-regulated in the oss40-1, oss40-7, and oss40-12 mutants, but up-regulated in the oss40-13 and oss40-14 mutants, indicating coordinated regulation among OsS40 members. These results suggest that OsS40-1, OsS40-7, OsS40-12, OsS40-13 and OsS40-14 are senescence-associated genes, involved in the senescence and carbon allocation network by modulating other OsS40 members, SWEET member genes and senescence-related gene expression.